Clinical, Biochemical, and Radiological Characteristics of a Single-Center Retrospective Cohort of 705 Large Adrenal Tumors - Iñiguez-Ariza, Nicole M. (Mayo Clin Proc Innov Qual Outcomes, 2017)
OBJECTIVE: To characterize large adrenal tumors (≥4 cm in diameter) and to identify features associated with malignancy. PATIENTS AND METHODS: We investigated the clinical, biochemical, and imaging characteristics in a large retrospective single-center cohort of patients with adrenal tumors of 4 cm or more in diameter during the period of January 1, 2000, through December 31, 2014. RESULTS: Of 4085 patients with adrenal tumors, 705 (17%) had adrenal masses measuring 4 cm or more in diameter; of these, 373 (53%) were women, with a median age of 59 years (range, 18-91 years) and median tumor size of 5.2 cm (range, 4.0-24.4 cm). Underlying diagnoses were adrenocortical adenomas (n=216 [31%]), pheochromocytomas (n=158 [22%]), other benign adrenal tumors (n=116 [16%]), adrenocortical carcinomas (n=88 [13%]), and other malignant tumors (n=127 [18%]). Compared with benign tumors, malignant tumors were less frequently diagnosed incidentally (45.5% vs 86.7%), were larger (7 cm [range, 4-24.4 cm] vs 5 cm [range, 4-20 cm]), and had higher unenhanced computed tomographic (CT) attenuation (34.5 Hounsfield units [HU] [range, 14.1-75.5 HU] vs 11.5 HU [range, −110 to 71.3 HU]; P<.001). On multivariate analysis, older age at diagnosis, male sex, nonincidental mode of discovery, larger tumor size, and higher unenhanced CT attenuation were all found to be statistically significant predictors of malignancy. CONCLUSION: The prevalence of malignancy in patients with adrenal tumors of 4 cm or more in diameter was 31%. Older age, male sex, nonincidental mode of discovery, larger tumor size, and higher unenhanced CT attenuation were associated with an increased risk for malignancy. Clinical context should guide management in patients with adrenal tumors of 4 cm or more in diameter.